EXPRESSION OF ERG IMMUNOHISTOCHEMICAL STAIN IN PROSTATIC ADENOCARCINOMA - Nabi, Sana Ghulam; Khan, Erum; Mushtaq, Sajid; Hassan, Usman; Hussain, Mudassar (Pakistan Armed Forces Medical Journal, 2021)
Objective: To investigate the incidence ERG fusion positive adenocarcinoma and its correlation with gleason grade and gleason group. Study Design: Cross-sectional study. Place and Duration of Study: Shaukat Khanum Memorial Cancer Hospital & Research Centre (SKMCH & RC), Lahore Pakistan, from Jan 2018 to Jan 2019. Methodology: A total of 100 cases of prostatic adenocarcinoma were retrieved and ERG immunohistochemical stain was applied on all these cases. ERG expression, extent of staining, percentage of tumor cells positive for ERG, pattern of staining was recorded. We found out relationship of ERG expression and gleason grade/gleason group. Results: ERG expression was seen in 62/100 (62%) cases. Mean patient age of ERG positive prostatic adenocarcinoma patients was 69.68 years. In GG1 (14.5%) 9 cases exhibited ERG positivity. In GG2-3, 41.93% cases and in GG4-5, 43.54% cases showed ERG expression. Conclusion: To conclude, age of presentation of ERG positive adenocarcinoma was high. ERG expression was seen in 62% of our cases which was much higher than reported in other Asian countries. In our study we found a significant correlation between ERG expression and high gleason grade group.